2016
DOI: 10.1002/oby.21622
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing food fussiness in children with obesity leads to greater weight loss in family‐based treatment

Abstract: Objectives Food fussiness (FF), or the frequent rejection of both familiar and unfamiliar foods, is common among children and given its link to poor diet quality, may contribute to the onset and/or maintenance of childhood obesity. The current study examined child FF in association with anthropometric variables and diet in children with overweight/obesity participating in family-based behavioral weight loss treatment (FBT). Change in FF was assessed in relation to FBT outcome, including whether change in diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 40 publications
1
18
2
Order By: Relevance
“…The present study shows that picky eating is prevalent in preschoolers with overweight and obesity. As Hayes et al [ 7 ] recently showed, picky eating may play a role in obesity treatment and should therefore be addressed by healthcare professionals. Parents of picky eaters in the obesity group perceived their child’s weight to be lower and 35% perceived their child to have normal weight; these parents also showed a non-significant trend towards not being as concerned about the child’s weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study shows that picky eating is prevalent in preschoolers with overweight and obesity. As Hayes et al [ 7 ] recently showed, picky eating may play a role in obesity treatment and should therefore be addressed by healthcare professionals. Parents of picky eaters in the obesity group perceived their child’s weight to be lower and 35% perceived their child to have normal weight; these parents also showed a non-significant trend towards not being as concerned about the child’s weight.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, picky eating also exists in children with overweight and obesity [ 5 , 6 ]. In a family-based obesity intervention with preschool children, a reduced degree of picky eating was associated with greater weight reduction [ 7 ]. This demonstrates that picky eating may play an important role in overweight and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…The current analysis only includes data from the initial weight loss phase in which all families received the same 16‐session FBT. In brief, FBT promotes a reduced‐energy‐dense diet and an increase in the consumption of nutritious foods, increased physical activity, and responsive parenting skills, such as routines, limit setting, and positive reinforcement (see for a detailed description of the program). While not designed to treat ED pathology, FBT included content that targeted aspects of ED pathology (e.g., emotional eating).…”
Section: Methodsmentioning
confidence: 99%
“…In older children, picky eating has also been shown to be associated with the development of psychopathology and poor family functioning ( 14 ). Picky eating behavior has been linked to both underweight ( 15 , 16 ) and overweight ( 17 19 ) in various studies, and a recent systematic review corroborates these conflicting findings, indicating a problem with inconsistent operational definitions ( 20 ). A recent longitudinal analysis revealed no relationship between picky eating and weight gain over time ( 21 ).…”
Section: Introductionmentioning
confidence: 99%